Utilization of the public space in gelanggang olahraga area H. Agus Salim Padang - Afriani Nanda Sari; Afriva Khaidir (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2018)
Public space is the most important component in urban spatial planning. Public space can be interpreted as a place or space that can be accessed or utilized by all communities or communities can gather for the same purpose. With the existence of public space the community can establish direct social interaction. So public spaces in urban areas can provide physical and psychological benefits to users. The research approach used is a qualitative approach with a descriptive research type. The selection of informants in this study used purposive sampling. The data collection techniques and tools used in three ways are nonparticipant observation, interviews and documentation. To achieve the validity of the research data using triangulation techniques. Meanwhile the data analysis technique uses technical analysis of Miles and Huberman data, namely data reduction, data presentation and conclusion drawing. The results of this study can be concluded (1) Strategic location, (2) Easy access, (3) areas that have attraction, (4) Weak social control.